The visual guide to Minecraft dig into Minecraft with this (parent-approved) guide full of tips, hints, and projects! - Clark, James H.; Dusmann, Cori; Moltz, John (Peachpit Press, 2015)
Annotation
Includes index. - Online resource; title from title page (Safari, viewed November 17, 2014)
Keywords: Minecraft (Game) -- Handbooks, manuals, etc; Video games -- Handbooks, manuals, etc; Adventure video games -- Handbooks, manuals, etc; Minecraft (Jeu); Guides, manuels, etc; Jeux vidéo; Guides, manuels, etc; Jeux vidéo d'aventure; Guides, manuels, etc; Adventure video games; Minecraft (Game); Video games; Handbooks and manuals